Doktrin Juridische/Systematische Specialiteit dalam Tindak Pidana Penyalahgunaan Sumbangan Dana Kampanye dan Pencucian Uang - Yanuar, Muh. Afdal (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2025)
The principle of lex specialis derogat legi generali frequently proves inadequate in resolving normative conflicts, particularly between Article 339(1)(c) of the General Election Law and provisions in the Money Laundering Law (UU TPPU). The present article examines the use of the doctrine of juridische/systematische specialiteit as a more effective approach to addressing such legal overlaps. The objective of this study is to ascertain which legal norms apply in instances where the acceptance of campaign contributions intersects with money laundering offences. Utilising normative legal research methodologies, bolstered by conceptual and juridical analysis, this study ascertains that the doctrine of juridische/systematische specialiteit confers enhanced legal certainty in resolving conflicts between overlapping criminal provisions. This doctrine is consistent with the principles that guide the interpretation of criminal norms and ensures a more precise application of the law. The article concludes that, in cases involving the proceeds of suspected money laundering from election campaign contributions, the provisions of the Money Laundering Act should take precedence over those in the Election Act. This approach not only supports systematic legal interpretation but also strengthens the legal framework in combating financial crimes involving political funding.